1977
DOI: 10.3109/00016347709158354
|View full text |Cite
|
Sign up to set email alerts
|

Carpal Tunnel Syndrome in Ovariectomized Women

Abstract: Electrophysiological parameters were studied in 32 gynecological patients before and after major gynecological surgery. No changes in maximal nerve conduction velocity or simple reaction time could be found after either hysterectomy or ovariectomy. Of the 20 ovariectomized patients, 3 developed subjective symptoms and electrophysiological signs of the carpal tunnel syndrome within a few months after surgery. Thus the carpal tunnel syndrome, which is common in women of menopausal age, seems to be precipitated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
1
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 10 publications
0
14
1
1
Order By: Relevance
“…Także owariektomia, hormonalna terapia zastęp-cza i menopauza wymieniane są jako czynniki sprzyjające powstaniu zespołu cieśni nadgarstka (30,31). Stwierdzono, że ryzyko konieczności chirurgicznego odbarczenia nerwu pośrodkowego w kanale nadgarstka wzrasta o 80% u pacjentek stosujących hormonalną terapię zastępczą (29).…”
unclassified
“…Także owariektomia, hormonalna terapia zastęp-cza i menopauza wymieniane są jako czynniki sprzyjające powstaniu zespołu cieśni nadgarstka (30,31). Stwierdzono, że ryzyko konieczności chirurgicznego odbarczenia nerwu pośrodkowego w kanale nadgarstka wzrasta o 80% u pacjentek stosujących hormonalną terapię zastępczą (29).…”
unclassified
“…None of the case group had hypothyroidism, diabetes, or was pregnant at the time of symptom onset. Although we did not directly inquire whether women were menopausal, five of 19 cases were older than 45, compared with four of 37 non-cases. This difference was not statistically significant (p > 0.10,…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%
“…Some of these predisposing states--including wrist fracture, arthritis, cysts, and acromegaly--can be explained on a purely mechanical basis since, as the tunnel becomes smaller or the contents become larger, compression of the tunnel contents occurs. Uther related disease states or conditions, including diabetes, hypothyroidism, dialysis, pregnancy, oral contraceptive use, menopause, and perhaps Vitamin 86 deficiency, appear to predispose individuals to the development of CTS through complex nutritional, vascular, and biochemical, as well as anatomical factors (13)(14)(15)(16)(17)(18)(19) demonstrated pressure increases within the carpal tunnel when both the wrist and the fingers are flexed (20,21). In several case series--notably those of Tanzer, Hybbinette and Mannerfelt, Birkbeck and Beer, and Gainer and Nugent--the authors noted that occupations "involving considerable use of the hands" appeared to predispose individuals to carpal tunnel syndrome (20,(22)(23)(24).…”
mentioning
confidence: 99%
“…The recommended criteria for making a medical diagnosis of CTS are: 1) the patient's report of the above symptoms, especially those localized to the distribution of the median nerve, and either 2) certain positive signs elicited by the clinician during physical exmination (e.g., Tine1 sign, Phalen test, or diminished sensation); or 3) electrodiagnostic findings indicative of median-nerve dysfunction across the carpal tunnel [Dawson et al, 1983;MMWR, 19891. A commonly cited risk factor for CTS is gender, with women consistently found to have a higher rate than men [Hall, 19861. In one of the few population-based studies of CTS incidence, for example, Stevens et al [1988], using a medical-records linkage system, found that adult women living in Rochester, Minnesota, had a rate nearly three times as great as the rate for men. Part of the excess caseload in women is probably due to differences in the distributions of specific medical and physical risk factors, such as pregnancy [Ekman-Ordeberg et al, 1987;McLennan et al, 19871, hysterectomy with ovariectomy [Bjorkqvist et al, 1977;Cannon et al, 19811, rheumatoid arthritis and other conditions [Hall, 19861, and possibly wrist shape [Johnson et al, 19831. In addition, there is mounting evidence that many women are exposed to high-risk activities at work, involving primarily repetitive and forceful movements of the hands and wrists [Armstrong and Chaffin, 1979;Cannon et al, 1981;Feldman et al, 1983;Silverstein et al, 1987al.…”
Section: Introductionmentioning
confidence: 99%